Detecting Earning Management of Companies Listing on HOSE - Quy, Vo Thi; Nhan, Duong Trong (Asian Journal of Social Sciences and Management Studies, 2017)
The study is aimed to detecting earning management from companies listing in Ho Chi Minh Stock Exchange (HOSE) during the period from 2013 – 2015 by using 2 models, Jones (1991) and Modified Jones Model developed by Dechow et al. (1995). Moreover, we also tested the effectiveness of Jones (1991) for detecting firms’ earning management since prior researches showed that Jones (1991) has lower standard error in detecting accruals based earning management compared with other models as suggested by DeAngelo et al. (1994). Hence we proposed that Jones (1991) provides a more significant outcome for estimating the nondiscretionary component of accruals and thus less exposed to misspecifications error from absent variables. We found that Jones (1991) illustrates a better explainable ability even though the adjusted R-square of the models is closely similar with each other.